Characterization of the complete mitochondrial genome of the Yushu yak (Bos grunniens). Issue 1 (2nd January 2019) - Guo, Xian; Bao, Pengjia; Chu, Min; Song, Rende; Ding, Xuezhi; Wu, Xiaoyun; Xiong, Lin; Liang, Chunnnian; Pei, Jie; Yan, Ping
Abstract: Yushu yak ( Bos grunniens ) is a local breed of yaks with strong adaptation to the high-altitude, cold, and anoxic environments. In this study, its complete mitochondrial genome was assembled from Illumina sequencing data. The genome was determined to be 16, 324 bp in size with a moderately asymmetric nucleotide composition (61.0% A + T) and encodes the typical set of 37 mitochondrial genes. The PCGs are initiated with the typical ATA or ATG codons and are terminated with TAA, TAG, or the incomplete stop codon T––. Phylogenetic analysis suggests that Yushu yak is most closely related to Qinghai Plateau yak.